Proposição de um framework conceitual do front end da inovação para universidades - Lopes, Cristina Lúcia Janini (Universidade Federal de São Carlos, 2021)
In recent decades, universities around the world have been structured to act more comprehensively, providing the fulfillment of their third mission, which is economic and social development. More active in the field of innovation and entrepreneurship, many universities have sought mechanisms that allow them to get closer to society and to transfer technological knowledge, without compromising the essence of academic work. In this context, the objective of this thesis is to propose a conceptual framework of the Front End of Innovation for Brazilian universities, stimulating science, technology and innovation, in order to contribute to the establishment of an environment more conducive to the promotion of innovation in Brazil. This research is supported by a systematic literature review in which 123 articles were analyzed, from the question about entrepreneurial university and 91 articles, from the question of the Front End of Innovation. From an empirical point of view, case studies were carried out with researchers who have licensed technology from three universities that are part of the INPI patent ranking (Brazilian Institute of Intellectual Property, 2020) – USP, UNICAMP and UFSCar. Semi-structured interviews applied to the 22 responding researchers were carried out. The information obtained was processed using the QSR Nvivo 11 software and content analysis and the results presented discuss the elements and activities of the Front End of Innovation in universities. The study made it possible to identify 4 components of the EIF distributed in 32 activities, namely: Influence Factors, Opportunities and Ideas, Concept Development and Actors Network. This last component is a central point of the FEI-U, as the network of actors that identifies, connects and interacts with the other components. Finally, it is believed that this research contributes from a theoretical and practical point of view, allowing the development of a conceptual model that contributes to the innovation process in universities.
Proposal of a conceptual framework for the front end of innovation for universities
Keywords: Universidade empreendedora; Processo da inovação; Transferência de tecnologia; Front End da Inovação; Entrepreneurial university; Innovation process; Technology transfer; Framework; Front end of innovation; ENGENHARIAS::ENGENHARIA DE PRODUCAO